Lamprey Immune Protein Mediates Apoptosis of Lung Cancer Cells Via the Endoplasmic Reticulum Stress Signaling Pathway - Song, Xiaoping; Xu, Xiangting; Lu, Jiali; Chi, Xiaoyuan; Pang, Yue; Li, Qingwei (Frontiers in Oncology, 2021)
Lamprey immune protein (LIP), a novel protein derived from the Lampetra japonica, has been shown to exert efficient tumoricidal actions without concomitant damage to healthy cells. Our study aimed to ascertain the mechanisms by which LIP inhibits lung cancer cells, thus delineating potential innovative therapeutic strategies. LIP expression in lung cancer cells was evaluated by western blotting and immunohistochemistry. Functional assays, such as high-content imaging, 3D-structured illumination microscopy (3D-SIM) imaging, flow cytometry, and confocal laser scanning microscopy, were performed to examine the proliferation and lung cancer cell apoptosis. Tumor xenograft assays were performed using an in vivo imaging system. We observed that LIP induces the decomposition of certain lung cancer cell membranes by destroying organelles such as the microtubules, mitochondria, and endoplasmic reticulum (ER), in addition to causing leakage of cytoplasm, making the maintenance of homeostasis difficult. We also demonstrated that LIP activates the ER stress pathway, which mediates lung cancer cell apoptosis by producing reactive oxygen species (ROS). In addition, injection of LIP significantly retarded the tumor growth rate in nude mice. Taken together, these data revealed a role of LIP in the regulation of lung cancer cell apoptosis via control of the ER stress signaling pathway, thus revealing its possible application in lung cancer treatment.